PENGARUH ELEMEN-ELEMEN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA MENGAJAR GURU MELALUI KOMITMEN AFEKTIF PADA PEKERJAAN SEBAGAI VARIABEL INTERVENING - Eka Destriyanto Ayuningtyas (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2017)
This research aims to test the impact of transformational leadership to the effective occupational commitment anda teaching performance. This research used population method (sensus) with 70 Teachers in SMA Negeri 3 Ponorogo as the responden. This research use path analysis. Based on the research, the elements of transformational leadership are strongly influence teaching performance, directly and indirectly through affective occupational commitment. For this school, headmaster must be someone who has transformational leadership style; in order to raise teaching performance and build teacher’s affective commitment in their job.